2017
DOI: 10.3389/fnagi.2017.00346
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Presbycusis and Tinnitus in a Portuguese Older Population

Abstract: Introduction: Presbycusis or age-related hearing loss (ARHL) is a ubiquitous health problem. It is estimated that it will affect up to 1.5 billion people by 2025. In addition, tinnitus occurs in a large majority of cases with presbycusis. Glutamate metabotropic receptor 7 (GRM7) and N-acetyltransferase 2 (NAT2) are some of the genetic markers for presbycusis.Objectives: To explore patterns of hearing loss and the role of GRM7 and NAT2 as possible markers of presbycusis and tinnitus in a Portuguese population s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…The latest study to assess GRM7 risk variants in an ARHL population sample tested four SNPs in elderly Taiwanese and found one associated in a dominant pattern (Chang et al, 2018). Two studies have analyzed GRM7 risk variants in relation to traits linked to ARHL; noise-induced HL in a Han Chinese sample (Yu et al, 2018) and tinnitus and ARHL in a Portuguese sample (Haider et al, 2017).…”
Section: And Idate G Ene S Tud Ie Smentioning
confidence: 99%
“…The latest study to assess GRM7 risk variants in an ARHL population sample tested four SNPs in elderly Taiwanese and found one associated in a dominant pattern (Chang et al, 2018). Two studies have analyzed GRM7 risk variants in relation to traits linked to ARHL; noise-induced HL in a Han Chinese sample (Yu et al, 2018) and tinnitus and ARHL in a Portuguese sample (Haider et al, 2017).…”
Section: And Idate G Ene S Tud Ie Smentioning
confidence: 99%
“…Several researches suggest that hearing loss contributes to the higher prevalence of tinnitus [33]. At present, the following two reasons are mostly considered.…”
Section: The Association Between Presbycusis and Tinnitusmentioning
confidence: 99%
“…Clinically, patients with presbycusis usually perform worse than others in function of speech and communication, resulting in negative psychosocial endings such as social isolation and social frailty [40]; depression, poor cognitive performance and even induce cognitive decline [33,41]; and low physical performance and physical frailty [42,43]. A meta-analysis of 36 epidemiological studies and 20,264 participants showed that the decline of cognitive domains are significantly associated with ARHL [44].…”
Section: The Association Between Presbycusis and Cognitive Declinementioning
confidence: 99%
“…Individual differences in the presentation, duration and frequency of these phantom sounds suggests that tinnitus is likely to be a heterogeneous condition representing a range of pathologies. It often manifests as secondary to hearing loss in both permanent hearing loss or temporary loss secondary to recreational or occupational noise exposure 1 7 . Although most individuals with tinnitus also have a hearing loss, tinnitus can occur in isolation 2 , 3 The relative contributions of the central and peripheral auditory system to tinnitus remain uncertain but evidence suggests that acute temporary tinnitus after noise exposure is likely to reflect cochlear damage while long term chronic tinnitus has been shown to involve re-organisation or disturbance of neurons in the primary auditory cortex owing to a lack of signal from the cochlea 1 , 8 .…”
Section: Introductionmentioning
confidence: 99%